A rare case of Ewing's sarcoma of the maxillary sinus - Amine Cherraqi, MD; Jihane El Mandour, MD; Basma Dghoughi, MD; Mohammed Tbouda, MD; Maria El Kababri, MD, PhD; Laila Hessissen, MD, PhD; Siham El Haddad, MD PhD; Nazik Allali, MD, PhD; Latifa Chat, MD, PhD (Radiology Case Reports, 2023)
Ewing's sarcoma is generally an aggressive, poorly differentiated bone and soft tissue tumor affecting children and young adults, it accounts for 4%-6% of all primary bone tumors and primary facial locations occur in only 1%-4% of all cases, primarily in the mandible and calvaria. Involvement of the paranasal sinuses is rare. Here we report the case of an 11-year-old girl with no medical, surgical, or traumatic history, who presented for 1 month and progressive evolution of swelling of the left cheek, associated with pain, nasal obstruction, rhinorrhea, and a slight weight loss not quantified. A craniofacial computed tomography (CT) scan showed a mixed lytic and condensing lesional tissue process centered on the left maxillary sinus, heterogeneously enhanced after contrast injection, lysing the walls of the sinus extended to the homolateral nasal cavity and slightly infiltrating the adjacent soft tissues. An incisional biopsy was performed and the pathological study proved that it was Ewing's sarcoma. She was put on neoadjuvant chemotherapy using 6 courses of vincristine, doxorubicin, ifosfamide, etoposide which resulted in a partial regression of the tumor size by 50%. Then the patient was put on combined chemotherapy and radiotherapy. A follow-up CT scan after 6 courses of vincristine, actinomycin, cyclophosphamide, and 17 sessions of radiotherapy showed lesion stability. Maxillary Ewing's sarcoma is a rare and aggressive tumor. Therefore, early diagnosis, combination therapy, and long-term follow-up are suggested in such cases to improve the survival rate.